Chloranilate bridged dinuclear copper(ii) complexes: syn–anti geometry tuned by the steric factor and supramolecular interactions. Issue 44 (25th October 2019) - Kar, Paramita; Franconetti, Antonio; Frontera, Antonio; Ghosh, Ashutosh
Abstract : The anti -conformation of chloranilate bridged di-copper complexes of NNO donor Schiff-base ligands is more stable than the syn -conformation, but the latter is stabilised by CH⋯π and hydrogen bonding interactions between solvent of crystallisation and chloranilate moieties. Abstract : Four dinuclear Cu(ii ) coordination compounds, [(CuL 1 )2 CA]·CH3 OH (1 ), [(CuL 1 )2 CA]·CH3 CN (1A ), [(CuL 2 )2 CA] (2 ) and [(CuL 3 )2 CA] (3 ) (where, CA = chloranilate anion, HL 1 = 2-[1-(2-dimethylamino-ethylimino)-methyl]-phenol, HL 2 = 2-[1-(2-methylamino-ethylimino)-methyl]-phenol, HL 3 = 2-[1-(methylamino-propan-2-ylimino)-ethyl] phenol, have been synthesized by the self-assembly of copper–Schiff base precursors together with chloranilate anions as bridging ligands. The complexes are characterized by elemental analyses, IR spectroscopy, thermal analyses, and single crystal X-ray crystallography. Structural analyses reveal that complexes 1 and 1A are in the syn -conformation while 2 and 3 are in the anti -conformation with respect to the metal coordinated Schiff-base ligands. Theoretical calculations show that for all three ligands, the anti -conformations are energetically favorable and the unfavourable syn -conformation in 1 or 1A is stabilized through CH⋯π and hydrogen bonding interactions between the [(CuL 1 )2 CA] unit and a co-crystallised solvent molecule. The M06-2X/def2-TZVP level of theory and NCI plot explicitly show that unlike in the case of 2 and 3, which form a 1D supramolecular chain by chelate ring⋯chelate ring π-stacking and cuprophilic interactions between neighbouring dimers, in 1 and 1A, steric interactions between neighbouring dimeric units, incorporated by one extra methyl group of the Schiff-base moiety, restrict these structures into dimeric units. Variable-temperature magnetic susceptibility measurements suggest weak antiferro- and ferromagnetic coupling in 1 ( syn -conformation) and 3 ( anti -conformation) with coupling constants of −2.11 and 3 cm −1, respectively.